The Role of Waqf in the Development of Islamic Education - Zakia, Maulida Ummi; Sabrina, Zafira; Syahputra, Jodi (AMK : Abdi Masyarakat UIKA, 2024)
Islam conceptually recognizes waqf organizations as resources that offer long-term benefits. Due to its good management, waqf contributes significantly to improving the quality of life of the community. Waqf has an important role in helping the implementation of education. Muslims learn more easily when they have waqf. Thanks to waqf, students who study Islam do not need to have a high financial burden, so both those who can and cannot afford it have equal access to education. To meet the needs of the community in the fields of religion, clothing, food, shelter, education, economy, health, and security, waqf seeks to build long-term and reliable financial flows. To achieve the pleasure of Allah SWT, waqf also seeks to uphold brotherhood and instill the ideals of solidarity and social solidarity.